Group Enrollment and Open Gym Format Decreases Cardiac Rehabilitation Wait Times. Issue 5 (September 2017) - Bachmann, Justin M.; Klint, Zachary W.; Jagoda, Allison M.; McNatt, Jeremy K.; Abney, Lesa R.; Huang, Shi; Liddle, David G.; Frontera, Walter R.; Freiberg, Matthew S.
Abstract : Purpose: Wait times for the first cardiac rehabilitation (CR) session are inversely related to CR participation rates. We hypothesized that changing from individually scheduled appointments to a group enrollment and open gym format, in which patients were enrolled during group intake sessions and could arrive for subsequent CR sessions any time during open gym periods, would decrease wait times. Methods: A total of 603 patients enrolled in CR at Vanderbilt University Medical Center from July 2012 to December 2014 were included in the study. We evaluated the effect of changing to a group enrollment and open gym format after adjusting for referral diagnosis, insurance status, seasonality, and other factors. We compared outcomes, including exercise capacity and quality of life, between the 2 groups. Results: Patients in the group enrollment and open gym format had significantly lower average wait times than those receiving individual appointments (14.9 vs 19.5 days, P < .001). After multivariable adjustment, the new CR delivery model was associated with a 22% (3.7 days) decrease in average wait times (95% CI, 1.9-5.6, P < .001). Patients completing CR had equally beneficial changes in 6-minute walk distance and Patient Health Questionnaire scores between the 2 groups, although there was no significant difference in participation rates or the number of sessions attended. Conclusions: Implementation of a group enrollment and open gym format was associated with a significant decrease in wait times for first CR sessions. This CR delivery model may be an option for programs seeking to decrease wait times. Abstract : Changing from individually scheduled appointments to a group enrollment and open gym format was associated with a 22% decrease in wait times for first cardiac rehabilitation sessions at Vanderbilt University Medical Center. Cardiac rehabilitation participation rates and increases in exercise capacity were not significantly different between the 2 groups.